Transcriptomic changes in the pre-implantation uterus highlight histotrophic nutrition of the developing marsupial embryo - Camilla M. Whittington (Nature Portfolio, 2018)
Abstract Early pregnancy is a critical time for successful reproduction; up to half of human pregnancies fail before the development of the definitive chorioallantoic placenta. Unlike the situation in eutherian mammals, marsupial pregnancy is characterised by a long pre-implantation period prior to the development of the short-lived placenta, making them ideal models for study of the uterine environment promoting embryonic survival pre-implantation. Here we present a transcriptomic study of pre-implantation marsupial pregnancy, and identify differentially expressed genes in the Sminthopsis crassicaudata uterus involved in metabolism and biosynthesis, transport, immunity, tissue remodelling, and uterine receptivity. Interestingly, almost one quarter of the top 50 genes that are differentially upregulated in early pregnancy are putatively involved in histotrophy, highlighting the importance of nutrient transport to the conceptus prior to the development of the placenta. This work furthers our understanding of the mechanisms underlying survival of pre-implantation embryos in the earliest live bearing ancestors of mammals.